SOUTH AFRICA’S MEDICINAL AND AROMATIC FLORA - A TREASURE CHEST OF OPPORTUNITIES FOR SCIENCE AND INDUSTRY - Viljoen, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The pharmaceutical, fragrance and flavour industries remain challenged and under immense consumer pressure to produce innovative and efficacious products for this lucrative industry. In a quest to satisfy consumer expectations and to produce products with some competitive edge, these industries most often turn to nature for guidance, inspiration and as a source of novel compounds for commercial development. South Africa represents a global epicenter of medicinal and aromatic plants. Despite this rich botanical diversity (matched by chemical diversity) it is surprising that many of the indigenous assets remain latent and are not systematically studied which is an obvious pre-requisite for these unique botanical assets to be transformed into consumer products. South Africa has offered the world two indigenous aromatic plants which have both been developed into a commercial success. Geranium oil (obtained from various cultivars of Pelargonium graveolens) and Buchu oil (from Agathosma betulina) are only two species of the over 1 000 aromatic plants indigenous to South Africa. Despite the extensive use of plants by the various ethnic groups in South Africa in the form of traditional medicines, South Africa (at this stage) cannot boast many international success stories derived from its indigenous medicinal plants. An extensive exploratory phase and efficient researching infrastructure underpins any commercial development. The paper is a brief reflection of past and present research and will unequivocally confirm the value, unique opportunities and constraints in exploring one of the most biodiverse areas in the world.